Self-Transformation of Cheryl Strayed Reflected in Wild (2014) Directed by Jean-Marc Vallée (2014) - Elsa Sopia Santika; Atinia Hidayah (Metaphor, 2025)
This study aims to analyze: (1) how traumatic experiences become the trigger for Cheryl Strayed’s journey in Wild (2014), and (2) how her self-transformation is reflected in the film, using Abraham Maslow’s theory of human needs. This research applies a descriptive qualitative method with the film Wild (2014) as the primary data source. Data were collected through observation, transcription of dialogues, classification of scenes, and interpretation based on psychological theory. The analysis reveals that Cheryl's personal traumas such as the death of her mother, drug use, and a failed marriage become the main motivations for her solo hike along the Pacific Crest Trail. Throughout the film, Cheryl gradually fulfills Maslow’s five levels of human needs, from physiological needs to self-actualization. The findings conclude that Wild is a narrative not only of physical survival but also of psychological healing and identity reconstruction.